2008
DOI: 10.1037/0735-7044.122.2.273
|View full text |Cite
|
Sign up to set email alerts
|

Masculinized finger-length ratios of boys, but not girls, are associated with attention-deficit/hyperactivity disorder.

Abstract: Gonadal hormones may exert permanent organizational effects on sexually dimorphic finger-length ratios and sexually dimorphic behavior expressed in childhood attention deficit-hyperactivity disorder (ADHD). This study extended recent work examining associations between finger-length ratios (specifically, 2D:4D) and ADHD in a well-characterized, clinically diagnosed, communityrecruited sample of boys and girls. A multistage, diagnostic procedure was utilized to identify 113 children with ADHD and 137 non-ADHD c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
74
3
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(91 citation statements)
references
References 53 publications
11
74
3
3
Order By: Relevance
“…Our results are also consistent with previous studies supporting associations between prenatal testosterone exposure and difficulties inhibiting impulses in boys but not in girls during childhood 8. For certain types of EF difficulties, such as inhibition, prenatal and postnatal effects of other hormones, such as estrogen, may play a role in shaping behavioral manifestations of EF.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are also consistent with previous studies supporting associations between prenatal testosterone exposure and difficulties inhibiting impulses in boys but not in girls during childhood 8. For certain types of EF difficulties, such as inhibition, prenatal and postnatal effects of other hormones, such as estrogen, may play a role in shaping behavioral manifestations of EF.…”
Section: Discussionsupporting
confidence: 93%
“…Similar associations were not found in girls,8 suggesting sex differences in effects of androgen exposure on EF deficits such as inhibition. A further study of children with CAH found higher rates of ADHD (which can include EF difficulties such as inattention and impulsivity) in boys compared to girls 10.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…Right hand digit ratios (length of the index finger to the length of the ring finger) are a proxy measure of foetal testosterone exposure, where smaller ratios are associated with high levels of prenatal testosterone exposure (Manning et al, 1998). Despite this measure of testosterone being somewhat controversial (Berenbaum et al, 2009), multiple studies reported that males diagnosed with ADHD or ASD have lower finger-length ratios, indicating an abnormally higher level of prenatal testosterone exposure (de Bruin et al, 2006;Martel et al, 2008). Similarly, a significant positive relationship was found between foetal testosterone levels and number of autistic traits in children by comparing foetal testosterone levels in the mother's amniotic fluid with their respective children's cognitive assessment results (Auyeung et al, 2009).…”
Section: Influence Of Sex Hormonesmentioning
confidence: 99%
“…Bu oransal farklılıkta prenatal sex steroidlerinin etken olduğunu gösteren kanıtlar mevcuttur (13). Bu oran depresyon, şizofreni, dikkat eksikliği hiperaktivite bozukluğu gibi psikiyatrik bozuklukların yanı sıra meme kanseri, prostat kanseri gibi hastalıklarda da incelenmiştir (14,15,16,17,18).…”
Section: Introductionunclassified